PsDMAP1/PsTIP60-regulated H4K16ac is required for ROS-dependent virulence adaptation of Phytophthora sojae on host plants - Fan Zhang; Shanshan Chen; Can Zhang; Zhiwen Wang; Jianqiang Miao; Tan Dai; Jianjun Hao; Xili Liu (Proceedings of the National Academy of Sciences, 2025)
Host plants and various fungicides inhibit plant pathogens by inducing the release of excessive reactive oxygen species (ROS) and causing DNA damage, either directly or indirectly leading to cell death. The mechanisms by which the oomycete Phytophthora sojae manages ROS stress resulting from plant immune responses and fungicides remains unclear. This study elucidates the role of histone acetylation in ROS-induced DNA damage responses (DDR) to adapt to stress. Mechanistically, the P. sojae DNA methyltransferase 1-associated protein (PsDMAP1) binds Tat-interactive protein 60 (PsTIP60) to comediate histone H4 acetylation on lysine 16 (H4K16ac). This regulation affects RNA polymerase II (pol II) recruitment, transcriptional induction of DDR-related genes, and the enrichment of histone H2Ax phosphorylated on serine 137 (γH2Ax) in response to both plant immunity and fungicide stress. The resulting H4K16ac serves as a crucial transgenerational epigenetic signal for virulence adaptation of P. sojae on plants, as a result of adaptation to ROS stress.